Are the self-employed at a higher poverty risk: empirical evidence from Serbian silc data - Ognjenovic, Kosovka; Pavlović, Dejana; Bodroža, Duško (Serbian Journal of Management, 2022)
Self-employment constitutes a significant share of the workforce in Serbia. Due to the equally high poverty as well as self-employment rates in Serbia, this paper aims to examine whether there is any prevalence between the two. Moreover, it also seeks to investigate what detriments exist within self-employment that keep or lead to poverty among self-employed people. The research is based on both longitudinal and cross-sectional SILC data. The main results indicated higher poverty exposure for solo entrepreneurs and those employed in family enterprises. Businesses run by men, low-skilled individuals, and young entrepreneurs are all at a much higher risk of poverty than other entrepreneurs or employees, especially those represented by women and highly educated individuals. The paper provides significant inputs for (1) managing differences within the active population at risk of income poverty and (2) monitoring outcomes of the self-employed, given that more than half of them are involved in the agricultural sector.